Change in the Upper Airway of Patients With Obstructive Sleep Apnea Syndrome Using Computational Fluid Dynamics Analysis: Conventional Maxillomandibular Advancement Versus Modified Maxillomandibular Advancement With Anterior Segmental Setback Osteotomy. Issue 8 (November 2015) - Kim, Taeyun; Kim, Hyoung-Ho; Hong, Sung ok; Baek, Seung-Hak; Kim, Kyung-Wuk; Suh, Sang-Ho; Choi, Jin-Young
Abstract : Objective: The aim of the study was to compare the effect of conventional maxillomandibular advancement (MMA) and modified MMA with anterior segmental setback osteotomy (MMA-ASSO) on the airway changes in patients with obstructive sleep apnea syndrome (OSAS) using three-dimensional computational fluid dynamics (3D-CFD) analysis. Methods: Two adult male patients with Class I malocclusion, lip protrusion, acute nasolabial angle, and OSAS were treated with conventional MMA (Case 1) and modified MMA-ASSO (Case 2). Individualized 3D airway models were fabricated using computed tomography data obtained 1 month before (T0) and at least 6 months after surgery (T1). A total of 7 cross-sectional areas of the airway were established, starting just above the hard palate (plane 1) with interval of 1 mm caudally. Airflow velocity and negative pressure were investigated using CFD analysis, and polysomnography studies were performed at T0 and T1. Results: There were improvement of apnea-hypoapnea index and the lowest O2 level (T0 versus T1; 43.2 versus 15.2, 79% versus 90% in Case 1; 61.0 versus 6, 89% versus 92% in Case 2). At plane 2 (retropalatal area) in Cases 1 and 2, there were increase in the smallest cross-sectional areas (57.9% versus 28.4%), decrease in the airflow velocity and increase in the negative pressure at the peak of expiration (49.5% versus 31.7%; 88.4% versus 54.3%), end after expiration (53.2% versus 32.2%; 83.2% versus 47.9%), and peak of inspiration (53.1% versus 29.2%; 75.3% versus 48.2%). Conclusion: Modified MMA-ASSO method might be an effective treatment option for OSAS patients with improvement of airway problems and esthetic facial profile.